Konjenital musküler tortikollis: Tanı ve tedavi seçenekleri - (:unkn) unknown (My University, 2012)
Konjenital musküler tortikollis (KMT), çocuklarda görülen tortikollisin en sık nedenidir. Bu çocuklar eşlik edebilecek deformiteler yönünden araştırılmalıdır. Bu çocuklarda aynı zamanda üst ekstremite kullanımında asimetri, kaba motor fonksiyonlarda gecikme, düşük kognitif fonksiyon, postür ve denge kontrolünde etkilenme saptanabilir. Dolayısıyla bu bebeklerde erken dönemde rehabilitasyon tedavisi başlanmalıdır. Eğer KMT’li çocuğun tedavisine ilk ayda başlanırsa tam düzelmenin %98’den fazla olduğu gözlenmektedir. Altı ay süreli konservatif tedaviden fayda görmeyen ve kraniyofasiyal deformitesi olan çocuklar cerrahi açısından değerlendirilmelidir. Türk Fiz Tıp Rehab Derg 2012;58:52-7.

Congenital muscular torticollis (CMT) is the most frequent reason of torticollis in children. Children with CMT should be examined for revealing concomitant deformities. Preferred use of one upper extremity, delayed acquisition of gross motor skills, decreased cognitive function below normal levels, abnormal postural patterns and balance control may also be seen in these children. Therefore, an early rehabilitation program should be initiated. Full recovery may be expected to be more than 98%, if treatment begins within the first month of life. Surgery should be considered for children, who do not benefit from conservative therapy within six months and who have craniofacial deformity. Turk J Phys Med Rehab 2012;58:52-7.
Congenital muscular torticollis: Diagnosis and treatment options
Keywords: Pediatri